Predictors of sexual behaviors among sexually active call center agents in iloilo City. - Simpal, Nursalim L. (2011.)
The rising incidence of Acquired Immune Deficiency Syndrome (AIDS) has alarmed the Philippine call center industry. As a response, this study investigated call center agents in Iloilo city. In particular, the predictors and kinds of sexual behaviors that call center agents engage in were investigated. These sexual behaviors may predispose call center agents to acquire AIDS. Through purposive sampling, 112 sexually active call center agents took part in this study. Using Hierarchical Regression, it was found that age, gender, sexual attitudes, and risky behavior predict sexual behavior. More specifically, gender and sexual attitude predicts fellatio (R2 = .237), gender predicts cunnilingus (R2 = .274), gender and sexual attitude predicts anal sex (R2 = .203), and gender predicts vaginal sex (R2 = .179), touching below the waist (R2 = .178) and touching the breasts (R2 = .268). In general, the results showed that all the predictor variables have low to medium effect sizes based on Cohen (1992). The findings imply that younger call center agents with positive sexual attitudes are more predisposed to engage in sexual behaviors, making them more susceptible to AIDS.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, UP Visayas, Miagao, Iloilo.
Keywords: Call Center Agents